SISTEM PENDUKUNG KEPUTUSAN SELEKSI ATLET TARUNG DERAJAT DENGAN METODE PROMETHEE - Arya Putrawan, I Putu; Sudarma, Made; Arsa Suyadnya, I Made (Jurnal SPEKTRUM; Vol 4 No 2 (2017): Jurnal SPEKTRUM, 2018)
Tarung Derajat is a martial art that has existed for a long time in Indonesia. Someone who wants to be an Tarung Derajat athlete must participate in the athlete selection. So far there is no system that facilitates the selection of Tarung Derajat athletes so that the selection process is more time-consuming, prone to error and nepotism. To prevent this, in this study built a decision support system using PROMETHEE method to assist the Tarung Derajat athletes selection process. This decision support system is built with web-based programming using PHP programming language and MySQL database. With success rate up to 90,66% in usability test, can be concluded that Decision Support System of Tarung Derajat Athletes Selection can support the athletes selection process.